Monitoring internal training load and salivary immune-endocrine responses during an annual judo training periodization - Agostinho, M. F.; Moreira, A.; Julio, U. F.; Marcolino, G. S.; Antunes, B. M. M.; Lira, F. S.; Franchini, E. (Journal of Exercise Rehabilitation, 2017)
The objective of this study was to examine the internal training load (TL), IgA, and salivary steroid hormone responses in elite youth judo athletes during an entire annual training periodization. Ten male judo athletes (18±2 years, 72.3±12.3 kg, and 175±6 cm) competing at a state/national level were examined for the TL and salivary imune-endocrine responses variations over an annual judo season, divided in three macrocyles composed by distinct periods denominated preparatory period (PP), competitive period (CP) and transition period (TP). At the end of PP and CP, saliva samples were collected to determine cortisol, testosterone and IgA concentrations. Throughout PP and CP the session-rating of perceived exertion and the total duration of each session were monitored, allowing the internal TL and weekly training strain (TS) calculation. During all macrocycles, significant decreases in TL and TS were observed during CP compared with PP (P<0.05), although no significant differences were observed for immune-endocrine concentrations between PP and CP (P>0.05). Specific variations were observed comparing periods with similar characteristics throughout the macrocycles as higher TL and TS (PP1 to PP2 and PP3, P<0.05), increased testosterone (CP1 to CP3, P=0.024) and decreased testosterone-cortisol ratio (PP1 to PP2, P=0.005). The present findings suggest that the internal TL variations over an annual multipeak traditional periodization did not influence the resting mucosal immune-endocrinal responses in young judo athletes.